Characteristics of multimode heat transfer in a differentially-heated horizontal rectangular duct - Wangdhamkoom, Panitan (Curtin University, 2007)
This study presents the numerical analysis of steady laminar flow heat transfer in a horizontal rectangular duct with differential heating on the vertical walls. Three heating configurations: one uniform wall temperature (CS1) and two linearly varying wall temperature cases (CS2 and CS3) are analysed. The study considers the combined effects of natural convection, forced convection and radiation heat transfer on the overall heat transfer characteristics. Air, which is assumed to be a non-participating medium, is chosen as the working fluid. A computational fluid dynamics solver is used to solve a set of governing equations for a range of parameters.For chosen duct aspect ratios, the numerical model simulates the flow and heat transfer for two main effects: buoyancy and radiation heat transfer. Buoyancy effect is represented by Grashof number, which is varied from 2,000 to 1,000,000. The effect of radiation heat transfer is examined by choosing different wall surface emissivity values. The weak and strong radiation effect is represented by the emissivity values of 0.05 and 0.85 respectively. Three duct aspect ratios are considered - 0.5, 1 and 2. The heat transfer characteristics of all the above heating configurations - CS1, CS2, and CS3 are analysed and compared. The numerical results show that, for all heating configurations and duct aspect ratios, the overall heat transfer rate is enhanced when the buoyancy effect increases. Since buoyancy effect induces natural circulation, this circulation is therefore the main mechanism that enhances heat transfer. Radiation heat transfer is found to significantly influence convection heat transfer in high Grashof numbers.